ANALISIS PENGARUH FEE AUDIT DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Properti dan Real estate yang Terdaftar di BEI Tahun 2022-2024) - Dian Anggraeni; Herry Laksito (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the impact of audit fees and audit committees on audit quality in the property and real estate sector in Indonesia. Audit fees are measured using the natural logarithm of audit service costs, while audit committees are proxied by the number of committee meetings held per year. Audit quality in this study is measured using a dummy variable based on the size of the public accounting firm, namely Big 4 and non-Big 4.The study population consists of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Using purposive sampling, a sample of 48 companies was obtained, with a total of 144 observations. The data analysis method employed in this study is logistic regression analysis.The results of the study indicate that audit fees have a significant positive effect on audit quality, while the audit committee has a significant negative effect on audit quality. Audit fees and the audit committee together have a positive effect on audit quality.